IMPLEMENTASI METODE TAKRIR DAN TASMI’ DALAM MENINGKATKAN KUALITAS HAFALAN SANTRI DI PESANTREN AL-ITQON JOGOROTO - siti karimah (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2021)
Abstract—This study aims to describe the implementation of the method of takrir and tasmi’, the implementation of the method of takrir and tasmi’ in improving the quality of rote students as well the halfactors that support and hinder. Dataacollectionatechniquesausingaobservation,ainterviewaand documentation. As for the result of the study : 1) The implementation of the method of takrir and tasmi’ goes well, it is based on the implementation of the activities of takrir and tasmi’. 2) The implementation of the method of takrir and tasmi’ have effectiveness in improving the quality of memorization of the students. 3) Supporting factors among others, istiqomah, intelligence and place, whikle the inhibiting factors, namely the lazy, mischievous and facilities. Keywords: Methods Takrir; Tasmi’; The Quality of Memorization Student